1979
DOI: 10.3382/ps.0580919
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Six Protein Quality Assays Using Commercially Available Protein Meals , ,

Abstract: The protein quality of 20 commercially available animal by-product meals (9 meat and bone meals, 6 feather meals, 3 fish meals, and 2 hair meals) was evaluated using chick protein efficiency ratio (PER), net protein utilization (NPU), pepsin digestibility, Tetrahymena furgasoni bioassay, dye-binding, and chemical score. The first limiting amino acid(s) in the animal proteins for chick weight gain were the total sulfur amino acids (TSAA) for both meat and bone meal and fish meals; however, methionine was the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The CV for AA ranged from 1.2% (Val) to 2.0% (His, Phe, and Cys) and 1.1% (Thr) to 5.0% (Met and Cys) for DES-BM and ECSP, respectively. The CP and AA composition of PBPM and FM samples compared well with previously published values (Daghir, 1975;Johnston and Coon, 1979;Baker et al, 1981;Papadopoulos et al, 1986;Wang and Parsons, 1998;Ravindran et al, 2005). The AA profile of PBPM and FM showed a somewhat similar trend, with Met and His ranking the lowest.…”
Section: Resultssupporting
confidence: 66%
“…The CV for AA ranged from 1.2% (Val) to 2.0% (His, Phe, and Cys) and 1.1% (Thr) to 5.0% (Met and Cys) for DES-BM and ECSP, respectively. The CP and AA composition of PBPM and FM samples compared well with previously published values (Daghir, 1975;Johnston and Coon, 1979;Baker et al, 1981;Papadopoulos et al, 1986;Wang and Parsons, 1998;Ravindran et al, 2005). The AA profile of PBPM and FM showed a somewhat similar trend, with Met and His ranking the lowest.…”
Section: Resultssupporting
confidence: 66%
“…Also, the pepsin test detected the lower digestibility of nitrogen in meat meal 1 compared with meat meal 2, although the sensitivity of the pepsin test would seem to be less than that of the in vivo assays. Johnston and Coon (1979a) found that the pepsin test correlated well with protein efficiency ratio measured with chicks, for a range of animal by-product meals. These workers used a more dilute solution of pepsin (0-002% (weight/volume)) than that used in this trial (0-2% weight/volume), so their test was likely to have been of greater sensitivity (Johnston and Coon, 1979b).…”
Section: Digestibility Trialsmentioning
confidence: 92%
“…As an alternative, several in-vitro digestibility assays have been developed, some of which have shown considerable promise (Satterlee et ul 1981). Earlier Rayner and Fox 1978; Johnston and Coon 1979) relied upon single enzyme digests. However, multi-enzyme assays more closely simulating conditions found in the live animal have been developed, and high correlations with in-vivo digestibility data have been reported (Akeson and Stahmann 1964; Saunders and Kohler 1972; Saunders t't crl 1973; Hsu et a1 1977;Buchmann 1979; Clunies and Leeson 1984).…”
Section: Introductionmentioning
confidence: 99%